The Effect of Good Corporate Governance, Profitability, Capital Intensity and Company Size on Tax Avoidance - Sigit Widiatmoko; Hadri Mulya (Journal of Social Science, 2021)
This study aims to determine the effect of independent boardof commissioners, institutional ownership, audit committee, profitability, capital intensity, and to determine the effect of company size on tax avoidance. So that the approach used in this research is a quantitative approach with this type of approach, namely explanatory research. The population in this study are all consumer goods companies that have been listed on the Indonesia Stock Exchange (IDX) in 2015-2019 as many as 53 companies. So that the sample used in this study is a non-probability sampling method which is included in the purposive sampling technique. This study produces an analysis which states that the independent board of commissioners and institutional ownership are declared to have no significant effect on Tax Avoidance in consumer goods companies listed on the IDX from 2015-2019. As for the audit committee, profitability, capital intensity, and also company size have a significant effect on tax avoidance in consumer goods companies that have been listed on the IDX for the 2015-2019 period.